STUDI EMPIRIS TERKAIT DENGAN PENGUNGKAPAN SUKARELA, KUALITAS AUDIT DAN ASIMETRI INFORMASI TERHADAP STOCK RETURN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR PADA BURSA EFEK INDONESIA - Sihombing, Jenny; Agoes, Sukrisno; Santoso, Urip (Fakultas Ekonomi dan Bisnis Universitas Tarumanagara, 2017)
This study used data of manufacturing companies listed on the Jakarta Stock Exchange (JSX) asÃ‚Â Ã‚Â unit of analysis. The purpose of this study is to find out the influence of voluntary disclosures and audit quality on information asymmetry. This study also aims to determine the effect of voluntary disclosure, audit quality and information asymmetry on stock return. In addition, this study aims to find out the ability of information asymmetry to mediate the effect of voluntary disclosure and audit quality on information asymmetry.This research used verificative-descriptive method with quantitative approach. The analytical method used in statistical data processing was path analysis. There are 132 manufacturing companies listed on JSX became the research samples of this study.The testing results shows that there are significant impact of voluntary disclosure and audit quality on information asymmetry. The testing results also show that there are significant impact of voluntary disclosure and information asymmetry on stock return, while the audit quality has no significant impact on stock return. At the same time, information asymmetry is significant to be the mediating variable on the impact of voluntary disclosure and audit quality towards stock return. Voluntary disclosure, audit quality and information asymmetry can be the determinant variables on Stock Return of manufacturing companies, listed on JSX.